Kinetic performance of cross-linked enzyme aggregates (clea)-amylase from Zophobas morio - Easa, Muhammad Noor; Yusof, Faridah; Abd Halim, Amanatuzzakiah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Many studies have been done on various species of insects to investigate their potential use in industries. This is because insects have high protein content which could be further manipulated. Due to its eating habit, Zophobas morio larvae, also known as supermeal worm has been shown to have high amylase activity. In this study, amylase from supermeal worm has been immobilized via Cross-Linked Enzyme Aggregates (CLEA) technique and its kinetic performance, evaluated. CLEA is one of the best immobilization technology in respect to enzyme stability and reusability. Kinetic performance of both free and CLEA-amylase were evaluated based on the Michaelis-Menten model. Results obtained based Hanes-Woolf, Lineweaver-Burk, Eadie-Hofstee and Hyperbolic Regression plots, showed that the kinetic parameters, Vmax and KM, changed upon immobilization. For CLEA-amylase, Hanes-Woolf plot had showed the best fitted model based on R2 with Vmax= 1.068 mM/min and KM= 0.182 mM. Lineweaver-Burk plot was used to obtain the kinetic parameters for free amylase, with Vmax and KM of 17.230 mM/min and 2.470 mM, respectively. The result from this study might open the new path in discovering the potential of using insects in industrial applications, for example, in detergent industry